The Correctness of the Organisational Structure - Marian HOPEJ; Magdalena HOPEJ-TOMASZYCKA; Anna ZGRZYWA-ZIEMAK (Communications of International Proceedings, 2020)
The article is an attempt to answer the question about the correctness of the organisational structure. The dominant literature view on structural solution correctness is based on the situational approach, standing that the structure is appropriate when it is adjusted to both external and internal circumstances. In the article, the shortcomings of situational appropriateness of the structure are discussed: the adjustment of the structure and context to each other is considered statically, conflicting demands on the shaping of different features of the structure and limited rationality of decision makers. Based on principle of the simplicity of the structural solution, the attempt to correctness of the structural solution, taking into account the time factor and – to a greater extent – the realities of management decisions, is developed.
Keywords: Organisational Structure; Simplicity; Management.